Expression Patterns Divergence of Reciprocal F1 Hybrids Between Gossypium hirsutum and Gossypium barbadense Reveals Overdominance Mediating Interspecific Biomass Heterosis - Li, Tengyu; Wang, Fuqiu; Yasir, Muhammad; Li, Kui; Qin, Yuan; Zheng, Jing; Luo, Kun; Zhu, Shouhong; Zhang, Hua; Jiang, Yurong; Zhang, Yongshan; Rong, Junkang (Frontiers in Plant Science, 2022)
Hybrid-breeding has provided an impetus to the process and achievement of a higher yield and quality of crops. Interspecific hybridization is critical for resolving parental genetic diversity bottleneck problems. The reciprocal interspecific hybrids and their parents (G. hirsutum and G. barbadense) have been applied in this study to elucidate the regulatory mechanism of early biomass heterosis. Phenotypically, the seed biomass, plant height over parent heterosis, leaf area over parent heterosis, and fresh and dry biomass were found to be significantly higher in hybrids than in parents. Analysis of leaf areas revealed that the one-leaf stage exhibits the most significant performance in initial vegetative growth vigor and larger leaves in hybrids, increasing the synthesis of photosynthesis compounds and enhancing photosynthesis compound synthesis. Comparative transcriptome analysis showed that transgressive down-regulation (TDR) is the main gene expression pattern in the hybrids (G. hirsutum × G. barbadense, HB), and it was found that the genes of photosystem I and ATP-binding may promote early growth vigor. Transgressive up-regulation (TUR) is the major primary gene expression pattern in the hybrids (G. barbadense × G. hirsutum, BH), and photosystem II-related genes mediated performance of early biomass heterosis. The above results demonstrated that overdominance mediates biomass heterosis in interspecific hybrid cotton and the supervisory mechanism divergence of hybrids with different females. Photosynthesis and other metabolic process are jointly involved in controlling early biomass heterosis in interspecific hybrid cotton. The expression pattern data of transcriptome sequencing were supported using qRT-PCR analysis. Our findings could be useful in theoretical and practical studies of early interspecific biomass heterosis, and the results provide potential resources for the theoretical and applied research on early interspecific biomass heterosis.